2020
DOI: 10.1038/s41598-020-59277-9
|View full text |Cite
|
Sign up to set email alerts
|

Step-wise elimination of α-mitochondrial nucleoids and mitochondrial structure as a basis for the strict uniparental inheritance in Cryptococcus neoformans

Abstract: in most sexual eukaryotes, mitochondrial (mt) DnA is uniparentally inherited, although the detailed mechanisms underlying this phenomenon remain controversial. the most widely accepted explanations include the autophagic elimination of paternal mitochondria in the fertilized eggs and the active degradation of paternal mitochondrial DnA. to decode the precise program for the uniparental inheritance, we focused on Cryptococcus neoformans as a model system, in which mtDnA is inherited only from the a-parent, alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…This observation led to the conclusion that the α nucleus leaves the parental cell and travels through the conjugation tube to join the a nucleus in the parental a cell. Recently, Nishimura et al [ 24 ] reported that the a nucleus is located inside of the conjugation tube. However, the images presented in Nishimura’s report do not allow unequivocal distinction of the assumed “zygote” from other neighboring cells.…”
Section: Cellular Features During Mating and Uniparental Mitochondmentioning
confidence: 99%
See 3 more Smart Citations
“…This observation led to the conclusion that the α nucleus leaves the parental cell and travels through the conjugation tube to join the a nucleus in the parental a cell. Recently, Nishimura et al [ 24 ] reported that the a nucleus is located inside of the conjugation tube. However, the images presented in Nishimura’s report do not allow unequivocal distinction of the assumed “zygote” from other neighboring cells.…”
Section: Cellular Features During Mating and Uniparental Mitochondmentioning
confidence: 99%
“…This observation suggests that uneven cytoplasmic mixing is unlikely to be the driving force of UMI. Contrary to the aforementioned model, Nishimura et al reported that a conjugation tube can originate from the a cell [ 24 ]. Thus, it remains to be established if the α nucleus migrates through the conjugation tube to meet the a nucleus on the other side of the zygote and if migration of organelles, including nuclei and mitochondria, follows the same dynamics of cytoplasm mixing.…”
Section: Cellular Features During Mating and Uniparental Mitochondmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, sperm mitochondria enter the egg at fertilization, but the zygotic ubiquitin-mediated proteolysis and autophagy machinery removes paternal mitochondria shortly after syngamy. [15,16] Basidiomycete yeast Cryptococcus neoformans, producing morphologically identical gametes of two mating types (a or α), eliminates mitochondrial nucleoids of the α parent post-fertilization, and then degrades the remaining α-mitochondrial structures through autophagy, [17] and there is similar nuclease-dependent mtDNA degradation in slime mould Physarum polycephalum. [18] Male fruit flies remove their mitochondria from maturing sperm before fertilization.…”
Section: Introductionmentioning
confidence: 99%